1979
DOI: 10.1161/01.cir.60.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Impaired left ventricular function in chronic aortic valve disease: survival and function after replacement by Björk-Shiley prosthesis.

Abstract: Postoperative survival and left ventricular function were studied in 128 patients who underwent isolated aortic valve replacement by the Björk-Shiley valve between 1973 and 1977. The average follow-up was 2.1 years. Patients with associated coronary artery disease or mitral valve disease were excluded. Preoperative ejection fraction ranged from 15-84%. Forty-two patients were restudied by cardiac catheterization 9.1 +/- 1.1 months (mean +/- SEM) after valve replacement. The hospital mortality was 11%. Preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…[235][236][237][238][239][240][241][242][243][244][245][246] With time, during which the ventricle develops progressive chamber enlargement and a more spherical geometry, depressed myocardial contractility predominates over excessive loading as the cause of progressive systolic dysfunction. This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[235][236][237][238][239][240][241][242][243][244][245][246] With time, during which the ventricle develops progressive chamber enlargement and a more spherical geometry, depressed myocardial contractility predominates over excessive loading as the cause of progressive systolic dysfunction. This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The American Heart Association (AHA) has established guidelines for the prophylaxis of SBE among predisposed patients." 2 …”
Section: Aortic Stenosismentioning
confidence: 99%
“…Kennedy and Schwarz et al [3,6] indi cated that reduced left ventricular pump func tion was reversible after successful aortic valve replacement regardless of preoperative aortic valve disease. Many previous reports showed that substantial left ventricular re modeling took place within the first few months following aortic valve replacement [3,25,26], On the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of evaluating left ventricu lar pump function after aortic valve replace ment for effective clinical management has replacement [3][4][5][6], In daily living, it is impor tant to assess cardiovascular reserve in pa tients with aortic valve replacement [7,8], However, the difference in the hemodynamic response during exercise after aortic prostheses between patients with aortic stenosis and aortic insufficiency has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%